2014
DOI: 10.3390/molecules19066941
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antipruritic Effects of Luteolin from Perilla (P. frutescens L.) Leaves

Abstract: Perilla (Perilla frutescens L.) leaves have shown therapeutic efficacy in the treatment of inflammatory disorders, allergies, bronchial asthma, and systemic damage due to free radicals. In the present study we analyzed the active constituents in perilla leaves using high-performance liquid chromatography (HPLC) and isolated luteolin, a polyphenolic flavonoid. We investigated the anti-inflammatory and antipruritic properties of luteolin. Luteolin inhibited the secretion of inflammatory cytokines such as interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 32 publications
1
76
1
Order By: Relevance
“…[40] The antiallergic activity of the plant extracts can be further attributed to the antiallergic and antihistaminic properties of luteolin. [41] The scientific data on kaempferol were antiallergic through mast cell stabilization [42] is in accordance with the results of the study.…”
Section: Discussionsupporting
confidence: 75%
“…[40] The antiallergic activity of the plant extracts can be further attributed to the antiallergic and antihistaminic properties of luteolin. [41] The scientific data on kaempferol were antiallergic through mast cell stabilization [42] is in accordance with the results of the study.…”
Section: Discussionsupporting
confidence: 75%
“…This makes sense some researcher argued that Luteolin from Perilla. frutescens L.leaves also significantly reduced the histamine release from rat peritoneal mast cells stimulated (Jeon et al, 2014) Antihistamine role in the management of asthma is widely documented (Wilson et al, 2006). In addition Lim et al demonstrated the inhibition of airways inflammation by the root of Angelica decurciva (Lim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Plants are an important source of these molecules and about 50% of drugs introduced into the market during the last 20 years have been derived directly or indirectly from small biogenic molecules (Vuorela et al, 2004;Basso et al, 2005). The anti-inflammatory, anti-allergic and immunomodulatory properties of plant extracts have been widely shown in several studies (Kim et al, 2004;Jeon et al, 2014). For instance, the use of herbal products, coffee or black tea, and over-the-counter medications as self-treatments among adults with asthma was shown (Blanc et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The antinociceptive effect of A. hierochuntica could be promoted by a group of constituents, which were extracted during preparation of AQAH and CHAH, such as flavonoids, alkaloids and others. The aqueous and alcoholic extracts of A. hierochuntica were reported to contain a number of bioactive constituents including apigenin, luteolin, quercetin and kaempferol [10,11] , which were found to have antinociceptive effect that appeared to be mediated by opioid system in a manner similar to the effects of morphine-like compounds [29,35,36] or by inhibition the secretion of inflammatory cytokines such as IL-1 β and TNF-α [29,37,38] . The antinociceptive effect of A. hierochuntica could be attributed to the single or synergetic action of these constituents or other components.…”
Section: Resultsmentioning
confidence: 99%